Evaluation of amniotic fluid volume and its relation to perinatal outcome - Dwivedi, Richa; Depan, Anju; Yadav, Kanti; Samariya, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In pregnancy amniotic fluid surrounds the foetus and plays an important role in the development of fetus. From the very beginning of the formation of the extracoelomic cavity amniotic fluid can be detected. To evaluate the predictive value of amniotic fluid index (AFI) (<5) for adverse perinatal outcome in terms of cesarean section for fetal distress, birth weight, meconium staining, Apgar scores, and NICU admission at birth. Methods: This was a prospective study of 100 antenatal women visited RMC, Ajmer, Rajasthan, India during the year 2018 with gestational age >34 weeks. The women’s history, clinical examination recorded, and AFI were measured and the perinatal outcome was compared between two groups, i.e., AFI <5 and >5. Results: The cesarean section rate for fetal distress, low birth weight babies, <2.5 kg and meconium staining was higher in patients with oligohydramnios (p=0.012, 0.001, 0.00015 respectively). There was no significant difference in Apgar score at 5 min <7 (p=0.087) and NICU at birth between the two groups. Conclusions: Oligohydramnios has a significant correlation with cesarean section for fetal distress, low birth weight babies and NICU admission.